COMPUTATIONAL PERFORMANCE COMPARISON OF MATHEMATICAL MODELS FOR MULTI-LEVEL REDUNDANCY ALLOCATION PROBLEM - Ahn, Namsu; Baik, Seungwon (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
The pursuit of high system reliability while dealing with limited resources such as cost, weight, and size is a crucial concern in various industrial sectors, particularly in military weapon systems. Redundancy of units is a widely recognized method for increasing reliability. In this research, we focus on the multiple-level redundancy allocation problem, which revolves around a series-parallel tree structure system. The main objective of the problem is to maximize the system's reliability while adhering to budget and path restrictions. Prior research has proposed integer non-linear programming formulations and heuristic approaches to address the problem. However, we propose an alternative solution using integer linear programming formulation to ensure the attainment of an optimal solution. To validate our proposed approach, we conducted performance comparison tests using 3-level and 4-level hierarchy tree data sets provided by previous research. The results demonstrate that our integer linear programming formulation surpasses the existing integer non-linear programming formulation in terms of the obtained system reliability and run time. Moreover, we observe that our formulation is capable of handling real-size instances of the problem effectively. By employing the integer linear programming approach, we can achieve better results in terms of system reliability and computational efficiency, making it a promising solution for tackling the multiple-level redundancy allocation problem in various practical applications.